Hallucinations and delusions associated with Parkinson's disease psychosis: safety of current treatments and future directions. Issue 7 (3rd July 2022) - Isaacson, Stuart H; Citrome, Leslie
ABSTRACT: Introduction: Over half of Parkinson's disease (PD) patients develop psychotic symptoms, and PD psychosis (PDP) is associated with significant distress to patients, caregiver burden, and impairs quality of life. Pharmacological therapy is limited to atypical antipsychotics. Areas covered: This review will summarize efficacy but will focus on the safety of antipsychotics for treating PDP, and in particular the off-target safety issues including cognitive impairment, sleep disturbance, cardiovascular effects, and motor function. Expert opinion: Pimavanserin is the only medication approved in the US for treating PDP, however clozapine is also considered efficacious. Despite lack of substantial evidence for efficacy, quetiapine is commonly used to treat PDP. Despite the effectiveness of pimavanserin and clozapine for treating PDP, a need exists for additional pharmacological agents that are effective for PDP while providing an acceptable safety and tolerability profile. Medications to treat PDP should avoid worsening motor function, and also minimize sleep disturbances, cognitive impairment, cardiovascular effects, and other non-motor safety concerns. A neutral effect or reduction in mortality risk associated with PD and PDP would be ideal, and low rate of discontinuation due to AEs is desirable. Lastly, medications that can be used safely in combination with other pharmacological agents is essential.